2013
DOI: 10.1002/cphc.201300926
|View full text |Cite
|
Sign up to set email alerts
|

The Non‐Ergodic Nature of Internal Conversion

Abstract: The absorption of light by molecules can induce ultrafast dynamics and coupling of electronic and nuclear vibrational motion. The ultrafast nature in many cases rests on the importance of several potential energy surfaces in guiding the nuclear motion-a concept of central importance in many aspects of chemical reaction dynamics. This Minireview focuses on the non-ergodic nature of internal conversion, that is, on the concept that the nuclear dynamics only sample a reduced phase space, potentially resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 73 publications
1
50
0
Order By: Relevance
“…The observation of an S 2 → S 1 transition faster than 150 fs implies a highly non-statistical process mainly activating a few reaction coordinates largely determined by Franck-Condon factors and the topology of the potential energy surface near the Franck-Condon region 44 . The current and previous 64 calculations predict the S 2 equilibrium structure to be boat-shaped and distorted out-of-plane relative to the Franck-Condon geometry (Figure 3), and thus early activation of prefulvene-like or boat-shaped modes is expected 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of an S 2 → S 1 transition faster than 150 fs implies a highly non-statistical process mainly activating a few reaction coordinates largely determined by Franck-Condon factors and the topology of the potential energy surface near the Franck-Condon region 44 . The current and previous 64 calculations predict the S 2 equilibrium structure to be boat-shaped and distorted out-of-plane relative to the Franck-Condon geometry (Figure 3), and thus early activation of prefulvene-like or boat-shaped modes is expected 66 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in comparison to IC, the importance and behavior of ISC in the ultrafast time regime are much less established. For IC, it has been shown that the ultrafast nature of the process rests on large degrees of non-ergodicity; 44,45 in other words, only a few vibrational modes are active during the transition. If the vibrations that are activated upon photon absorption couple different electronic surfaces, the possibility of an ultrafast transition is available and can occur within the timescale of the respective vibrational period.…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond time-resolved mass spectrometry (FTRMS) has brought about many discoveries pertaining to the electronic structure and initiated dynamics of polyatomic molecules, as well as to the understanding of (non)-ergodicity in chemical reactions. [1][2][3][4][5][6][7] Recently, this technique has been increasingly applied to studying the post-ionization dynamics of radical cations. [8][9][10][11][12][13][14][15][16][17] A major challenge in these experiments stems from the fact that ionization via multiphoton absorption typically produces vibrationally hot ions.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important because a profound understanding of photoinduced dynamics almost always necessitates a detailed comparison of experiment with theory. Many model systems have been investigated by time-resolved experiments [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] or dynamical simulations. [20][21][22][23][24][25][26] We believe that fundamental questions could be answered more easily by joint studies connecting experimental approaches with such simulations.…”
Section: Introductionmentioning
confidence: 99%